Application of Sharia Principles in Management Risk on Industry Insurance Sharia - Setya Pramono; Barizatutsani Barizatutsani; Nisrina Ulba; Widya Dian L (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
With the existence of sharia banking , banks carry out business in a way that complies with Sharia, known as Sharia principles. It consists of exchanging money in accordance with sharia principles while managing risk ( mudharabah ), managing money ( murabahah ), fairness or abundance ( ijarah ), or lending money from one bank to another ( ijarah wa iqtina ) and so on. In its development, institutions outside the banking structure, such as insurance, also participated. Insurance is a non-bank financial institution that operates in the economy outside the banking sector. It is tasked with supporting economic activities by providing investment and financing access services. The unique thing about sharia insurance is that it carries out procedures for all its activities with principles that are in line with sharia, so in all these cases it is also very important to see, measure, control and monitor risks that arise from operational activities. Therefore, the authors' skepticism regarding their hypothesis is whether or not there is an influence of sharia principles on risk management in sharia insurance. This research uses quantitative methods with descriptive statistical analysis . The impact of applying Islamic principles to risk management in the sharia insurance sector is that the application of Islamic principles to risk management in the insurance sector is very beneficial. However, there are parts that need to be limited and clarified as to what kind of disaster we can help with, of course this requires company regulations and customer agreements to be in good and correct accordance.